POTENTIAL CHIKUNGUNYA EPIDEMICS IN PAKISTAN: ACT BEFORE IT'S TOO LATE - Rehman, Khalid (Journal of Ayub Medical College Abbottabad, 2019)
First Chikungunya outbreak occurred in Karachi, Pakistan in 2016. Chikungunya is transmitted by the Aedes mosquito which is also transmits Dengue fever. The first Dengue fever outbreak of Pakistan also occurred in Karachi in 1994. In the past 23 years the disease has spread to all parts of the country. This is comprehensible as there is a lot of travelling between Karachi and other parts of the country which increases the chances of spread of the virus. Based on the precedent of Dengue fever in Pakistan, if appropriate preventive measures are not taken to control Chikungunya, it will only be a matter of time before it hits other parts of the country. At the same time International Health Regulations has to be practiced with all its zest to avoid introduction of diseases like Zika virus and yellow fever, which are also transmitted by Aedes. Keywords: Chikungunya; Dengue fever; IVM; Aedes mosquito